Formation of Professional Communicative Competence in University Students through the Use of Innovative Technologies - Musaeva Amina Karamatovna (International Journal on Orange Technologies, 2024)
We will consider in this article the procedure for using the "FSMU" technology, which will help teach students to think critically in Russian lessons. This technology can be used for the purpose of examining students ' subject coloring when addressing a debate, conducting a debate, or strengthening a topic. Because this technology teaches students to defend their opinion, to think freely and to pass their opinion on to others, to argue openly, while analyzing the knowledge acquired by students in the educational process, to the culture of assessing and arguing to what extent they occupy *5+.The implementation of FSMU technology takes place in several stages. In Phase 1, the teacher identifies with the students the subject of the debate, or the problem to be discussed, or the section studied, and provides information to the students in the training session that first each student works individually, then works in small groups, and finally works as a team at the end of the lesson, it is mentioned in the course of the exercise that each student can fully state their opinion freely. In Step 2, each student is handed out papers written in Step 4 of FSMU technology F-state your mind. S-indicate the reason for the statement of your opinion. M-give an example (proof) by proving the reason you specified.